How selectivity affects the accuracy and precision of chloride ion-selective electrodes based on quaternary ammonium salts - SHIBATA, Yasuhisa; MIYAGI, Hiroyuki; OZAWA, Satoshi; OKI, Naoto (BUNSEKI KAGAKU, 1994)
A study into how selectivity affects the accuracy and precision of chloride ion-selective electrodes (Cl-ISEs) used in the analysis of physiological fluids is presented. In this study, dimethyldioctadecyl-, tetraoctadecyl- and methyltridodecylammonium salts (DMDODA, TODA and MTDDA, respectively) were used as sensing materials. Control serum and healthy human urine samples were analyzed by Cl-ISEs and the interfering anions in these samples were examined by ion chromatography in order to study the relation between error and selectivity. It was found that errors in the analysis of these samples were mainly due to the sulfate ion, because good correlation between its concentration and error was observed. From the comparison of selectivity and Syx (standard deviation of y on x) obtained by three types of sensing materials, it was shown that a highly reliable Cl-ISE could be produced by an improvement of selectivity to hydrophilic anions such as sulfate ion without a strong affinity for lipophilic anions. Furthermore, it was also suggested that Cl-ISE should have a small selectivity factor to organic acid anions and drugs. The Cl-ISE based on TODA exhibited excellent selectivity and was applied to the analysis of patient physiological fluids (serum, plasma, urine); good accuracy and precision were obtained. Therefore, it is expected to be useful in the field of clinical analysis.